Meningkatkan Pemahaman Konsep dan Kesadaran Metakognisi Siswa pada Materi Struktur Atom Melalui Pemodelan - Musahidin, Musahidin; Muhali, Muhali; Asy’ari, Muhammad; Sukaisih, Roniati (Journal of Authentic Research, 2022)
Pemahaman konsep siswa pada materi struktur atom tergolong rendah sehingga menyebabkan kesulitan siswa dalam mengkonstruksi pengetahuan baru. Siswa bahkan tidak dapat menangkap konsep inti dari keseluruhan konsep yang dipelajari. Penelitian ini bertujuan untuk meningkatkan pemahaman konsep dan kesadaran metakognisi siswa pada materi struktur atom. Penelitian tindakan kelas yang dilaksanakan dalam dua siklus dan melibatkan 30 siswa kelas X IPA SMAN 2 Pujut dilakukan untuk mencapai tujuan penelitian. Tes pemahaman konsep berupa lima butir soal uraian dan Metacognitive Awareness Inventory (MAI) diadmisnistrasikan pada setiap siklus penelitian untuk mengidentifikasi pemahaman konsep dan kesadaran metakognisi siswa. Data penelitian dianalisis secara deskriptif melalui penentuan skor dengan skala 100. Peningkatan pemahaman konsep dan kesadaran metakognisi siswa juga dianalisis dalam penelitian ini menggunakan persamaan n-gain. Hasil penelitian menunjukkan pemahaman konsep siswa mencapai rata-rata 65,20 (siklus I) dan 75,47 (siklus II), dengan persentase ketuntasan sebesar 73,33% (siklus I) dan 86,67 (siklus II). Pemahaman konsep siswa juga ditemukan mengalami peningkatan setelah pembelajaran dengan kategori medium (n-gain= 0,30). Di pihak lain, kesadaran metakognisi siswa juga mengalami peningkatan dengan kategori medium (n-gain= 0,35) dengan rata-rata 63,02 (siklus I) dan 76,25 (siklus II). Hasil temuan tersebut menunjukkan bahwa penerapan pembelajaran pemodelan dengan alat peraga kimia sederhana dapat meningkatkan pemahaman konsep dan kesadaran metakognitif siswa kelas X IPA SMAN 2 Pujut pada materi struktur atom. Enhancing Conceptual Understanding and Metacognitive Awareness of Students on Atomic Structure through Modeling Abstract Understanding of the concept among students in atomic structure is considered low, resulting in difficulties for students in constructing new knowledge. Students are unable to grasp the core concept of the overall concepts being taught. This research aims to improve students' understanding of the concept and metacognitive awareness in the topic of atomic structure. A classroom action research was conducted in two cycles, involving 30 students from the 10th grade of Science Program at SMAN 2 Pujut, to achieve the research objectives. A concept comprehension test consisting of five essay questions and the Metacognitive Awareness Inventory (MAI) were administered in each research cycle to identify students' concept understanding and metacognitive awareness. The research data were analyzed descriptively by scoring with a scale of 100. The improvement in students' concept understanding and metacognitive awareness was also analyzed in this research using the n-gain equation. The results of the study indicate that students' concept understanding reached an average score of 65.20 (cycle I) and 75.47 (cycle II), with a mastery percentage of 73.33% (cycle I) and 86.67% (cycle II). Students' concept understanding also showed an improvement after the instruction with a medium level of improvement (n-gain = 0.30). On the other hand, students' metacognitive awareness also experienced an improvement with a medium level of improvement (n-gain = 0.35), with an average score of 63.02 (cycle I) and 76.25 (cycle II). These findings indicate that the application of modeling learning with simple chemical models can enhance students' concept understanding and metacognitive awareness in the topic of atomic structure among 10th-grade students at SMAN 2 Pujut.